The Singapore foreign exchange market : insights and prospects - Chua, Li Li (2015)
Historically, the role of the forex is to support commercial trade. However, in recent years, despite the growth in the total forex turn over, the proportion of forex transactions driven by trade has declined while the proportion related to risk-taking by large money-centre banks, central banks and multinational countries have increased. The numerous new instruments that have emerged in the last few decades have helped to boost the foreign exchange market further. The purpose of this project is to study the different components of this market. The spot market is the basis for the existence of the other derivative instrument market. It forms the largest portion of the total forex turnover. However, the participants are exposed to the exchange rate risks in this market and hence the evolution of other instruments that could hedge the risks and insure the value of the assets. The spot market will be discussed in chapter two. Forward contract is a very popular form of hedging arrangement. It is a private negotiation between the bank and the corporation. As such, it can be tailored to the needs of the corporation. Another similar instrument is the currency futures which involves buying or selling of a standardized amount of foreign currency on an organised exchange for delivery on one of the several standardised future dates. A brief comparison of the similarities and differences of the two contracts would also be dealt with in chapter three. A swap arrangement in the forex market involves a currency swap. Two counterparties will exchange principal amounts of different currencies at the prevailing spot rate. Over the term of the swap arrangement, periodic payment of interests are made in different currencies by the two parties. At maturity, the principal amounts would be re-exchanged. Therefore, a swap is effectively a forward arrangement. The foreign exchange options market is only a small proportion of the forex market. However, it is growing rapidly especially with increasing liquidity and knowledge of its benefits. A currency option allows the holder a right to receive or deliver a specified amount of the foreign currency at a specified price before expiration. It is unique because it can insure the value of the asset. This topic would be discussed in chapter four. The discussion on the different instruments in the forex market is ground work for the analysis of the Singapore Foreign Exchange Market. The efforts of the government in Singapore to develop Singapore as a financial centre has succeeded. This is evident in the booming equity market after the listing of Telecom shares. The futures market has become more significant as different types of futures instruments are introduced to tailor to different customer needs. The forex market is also expanding fast. Singapore has become the next largest foreign exchange dealing centre in the Asian time zone, after Tokyo. Hence the significance of studying this market in Singapore. Chapter five and six would be crux of the project which would analyse in detail the forex market in Singapore.